The Influence of Innovation Types towards Small Medium Enterprises Performance: A Study of Malaysian Manufacturing Industry - RAHIM, RAMITA ABDUL; Nik Mahmood, Nik Hasnaa; Masrom, Maslin (International Journal of Supply Chain Management, 2019)
Malaysian SMEs is very important to the country especially in contribution to creating more job opportunities, generating higher production volumes, increase export and many others. SMEs has been recognized because of the essential role that has been carried out towards the economic growth, but it is actually disappointed because the fact shows that the developments and performances of Malaysian SME considered low if compared to the others developing's country. Even though numerous government efforts have been and are being implemented over the years, SMEs performance is still not achieved as expected.  In addition, with globalization economy nowadays, SME also faced the difficulties in order to sustain and survive especially to compete with the foreign company.  The competition from the foreign company has forced SME to strategies their organization to be more competitive particularly through innovation performance. Therefore, this study has selected innovation as variables and aim to find out the influence of innovation towards Malaysian SME performance. This study measured innovation by four types of innovation namely product innovation, process innovation, administrative innovation, and marketing innovation.  SMEs performance was measured from the perspective of financial and non-financial.  The survey was conducted among top-level management of 440 Manufacturing SME in Malaysia. The data was analyzed through Statistical Package for the Social Sciences (SPSS) and the hypotheses were tested through regression analysis.   Keywords: Product innovation, process innovation, administrative innovation, marketing innovation, Small Medium Enterprises, Manufacturing, Malaysia.